Transference and Countertransference dalam Relasi Konseling - Hastuti, MM. Sri (Jurnal Orientasi Baru, 2010)
Both transference and countertransference essentially are natural projection of feelings and expections from an individual to another one which occurs spontaneously and unconsciously. The feelings that are unconsciously projected in transference and countertransference are very real, come from the center of ones being and are based upon past experience with other people or events. Transference and counter transference not only occurs in counseling, but in all of our relationship. However, if transference and countertransference occurs in the counseling relationship, both of them will affect the effectiveness of counseling process. Regarding transference or countertransference, reactions of counselor in counseling process to his/her counselee may not be related to the actual intervention. When counseling, it is important to be aware of some dangers inherent in transference or countertransference. The key is for the professional counselor to acknowledge the existence and significance of transference for the conselee and countertransference for the counselor.